Women Empowerment through ‘Kudumbashree’ Project of Kerala–a Micro level Analysis - A. Sakeer Husain; Anu S. Nair (Journal of Agricultural Extension Management, 2025)
Efforts towards women’s development have been initiated both by the government as well as the non-government agencies since 1950. Women’s development in recent years emphasizes on providing equal opportunities to women by removing gender bias; empowering women and creating self-reliance among them. In addition, it stresses on adoption of a holistic approach to women’s development, thereby providing inter-sectoral linkages with health, education, employment and training and other sectors concerning supportive and social welfare activities